Pola Asuh Permisif dan Ketidakberlanjutan Pendidikan Anak di Desa Banua Anyar Kabupaten Barito Kuala - Thiansyah, Adhera Nur; Zulaikha, Siti (Huma: Jurnal Sosiologi, 2026)
The phenomenon of children dropping out of school at the primary level in Banua Anyar Village reflects structural problems within the family and community, as the community does not understand the importance of education. This research aims to understand how parenting affects children's continuing education, especially in families that do not support basic education. children's education, especially in families that do not support basic education in Banua Anyar Village, Kabupaten Banua Anyar, Barito Kuala district. The main focus is on permissive parenting, which is characterized by low control, direction, and emotional support from parents. This research used a qualitative approach with a case study method. Data were collected through observation, interviews, and documentation, then analyzed using the Manual Data Analysis Procedure (MDAP). Manual Data Analysis Procedure (MDAP). The results showed, permissive parenting is not a form of parental negligence, but an adaptive response to difficult economic conditions, low levels of parental education, and narrow perceptions of education, as well as a narrow perception of the meaning of education. People parents prefer their children to help with household chores or work at school age rather than continuing their education because school is not school age than to continue their education, because school is not seen as an urgent need or means of social mobility. Children who grow up in this upbringing are deprived of the encouragement, direction, and long-term orientation that they should obtain from the family. The family's failure to socialize also causes educational institutions to lose their power.